Penggunaan Hyperlink dalam Materi Belajar dan Keaktifan Pembelajaran Siswa SMK di Papua Selama Pandemi Covid 19 - Samsudin Arifin Dabamona; Hasruddin Duta (SAP (Susunan Artikel Pendidikan), 2023)
This study aims to determine the effectiveness of learning techniques through online links and the learning activities of students of SMKN 3 Jayapura Class XI TKRO during the Covid 19 Pandemic. The study applied Classroom Action Research (CAR) as a research method during 4th semester 2020/2021. The research consisted of two cycles consisting of four elements: planning, implementation, observation and reflection. The study used information from observations, personal interactions, class group WA interactions and identification of student assignments (without assessment) to collect and analyze data. This research indicated that online learning by using a link reference strategy was able to improve the effectiveness of learning. Learning activity was increased through active interaction that was relevant to the material and the collection of tasks that exceed the predetermined indicator.